1996
DOI: 10.1111/j.1468-3148.1996.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Use of Psychoactive Medication Among People with Intellectual Disabilities Who Have Been Resettled from Long‐stay Hospitals into Dispersed Housing

Abstract: Aspects of the use of psychoactive medication were assessed among 118 adults with intellectual disabilities who had been resettled from long-stay hospitals into two local dispersed housing services. The resulting data indicated that (1) 69% of people were receiving psychoactive medication primarily for the control of challenging behaviour;(2) only 8% had psychiatric diagnoses; (3) polypharmacy was frequent and (4) medication was continued over long periods sometimes without review. The prescribing practices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 11 publications
3
31
0
Order By: Relevance
“…Previous studies have identified aggression as an important factor relating to requests for psychotropic medication (Fleming et al, 1996;Stolker et al, 2001). Our findings are consistent with this; the most frequent indication in our study for PRN prescribing being agitation and aggression.…”
Section: Discussionsupporting
confidence: 95%
“…Previous studies have identified aggression as an important factor relating to requests for psychotropic medication (Fleming et al, 1996;Stolker et al, 2001). Our findings are consistent with this; the most frequent indication in our study for PRN prescribing being agitation and aggression.…”
Section: Discussionsupporting
confidence: 95%
“…1990; Branford 1994; Etherington et al. 1995; Fleming et al. 1996) and about 10% of people living with their natural or substitute families (Clarke et al.…”
Section: Introductionmentioning
confidence: 99%
“…The two most frequent reasons that led to admission were challenging behaviours and mental health problems, and previous research verifies these as continuing needs of this population (Slevin 1995, Turkistani 2003, Slevin 2007). In addition, the study found that having challenging behaviour was significantly associated with longer stay in the unit and with use of antipsychotic medications, even though use of these medications for challenging behaviour has been questioned (Fleming et al. 1996, Reiss & Aman 1998, Ahmed et al.…”
Section: Discussionmentioning
confidence: 99%